Critical study of central venous pressure - Marx, Martín (Cirugía del Uruguay, 1973)
A restricted critical study of the true value of PVC pressure and reasons for its variations showed the importance of serial observations andof the indixes derJved from acute and belated reponses to the administration of liquids.